The Methodological Quality Scale (MQS) for intervention programs: validity evidence - Chacón-Moscoso, Salvador; Sanduvete-Chaves, Susana; Lozano-Lozano, José Antonio; Holgado-Tello, Francisco Pablo (Frontiers in Psychology, 2023)
Introduction A wide variety of instruments are used when assessing the methodological quality (MQ) of intervention programs. Nevertheless, studies on their metric quality are often not available. In order to address this shortcoming, the methodological quality scale (MQS) is presented as a simple and useful tool with adequate reliability, validity evidence, and metric properties. Methods Two coders independently applied the MQS to a set of primary studies. The number of MQ facets was determined in parallel analyses before performing factor analyses. For each facet of validity obtained, mean and standard deviation are presented jointly with reliability and average discrimination. Additionally, the validity facet scores are interpreted based on Shadish, Cook, and Campbell’s validity model. Results and discussion An empirical validation of the three facets of the MQ (external, internal, and construct validity) and the interpretation of the scores were obtained based on a theoretical framework. Unlike other existing scales, MQS is easy to apply and presents adequate metric properties. In addition, MQ profiles can be obtained in different areas of intervention using different methodologies and proves useful for both researchers doing meta-analysis and for evaluators and professionals designing a new intervention.